Integração de novos colaboradores: um estudo no Sicoob Alto Vale - Schafer, Cássio Ray (Universidade do Vale do Rio dos Sinos, 2019)
In the organizational environments, is very common have different types of employee profiles, with the most varied desires, problems, qualities and skills, what the people can imagine. Is known that leadership plays a fundamental figure in the management of teams and their attitudes are allied to the mission, vision, values and purpose of the company that will guide all the people inserted there. This job deals with a ‘’case study’’ about the integration of new collaborators in Sicoob Alto Vale. The specific objectives of the research are to present the existing models in the cooperative, to verify how is the process of integration of new collaborators in other cooperatives and propose improvements in the integration process. In the theoretical referential, the author addressed topics of great importance to the subject such as: training of employees and the work of leadership. The research was qualitative and descriptive in scope. The interview was the instrument of data collection used. Within the specific objectives of the work, it was sought to better understand the process of integration of new employees also in other cooperatives in order to propose improvements to the acctual process in Sicoob Alto Vale. The interviews were applied through videoconferences due to the practicality of gathering information. Among the results is worth noting that in one of the cooperatives analyzed, the integration process is mature and includes the individual development plan (PDI). Through the application of the case study, is possible to reflect in more depth that this theme is of fundamental relevance for the success of the organizational environment and for the continuous improvement of its climate.
Keywords: Integração; Colaboradores; Cooperativas; Integration; Contributors; Cooperatives